THE INDEPENDENT ACCOUNTANT. - Ashley, C.A. (The Accounting Review, 1942)
Abstract The Dominion Companies Act of 1934, amended in 1935, and the English Companies Act of 1929 have many sections, which are identical or almost identical, and this is particularly true of the sections that deal with the audit of accounts. Both acts require that the accounts of companies granted limited liability shall be audited by an auditor or auditors appointed annually by the shareholders in general meeting; that the auditor shall report to the shareholders; and that a copy of the balance sheet, profit and loss account, and auditor's report shall be sent to shareholders before their annual general meeting. In practice, of course, the management chooses the auditor, and the board of directors has the power to fill vacancies during the year in the office of auditor, but no change in the auditor can otherwise be made without notice being given in advance to the auditor and to the shareholders of intention to propose a change. The auditor is entitled to attend any meeting of shareholders at which the audited accounts are to be discussed.